Innovative approaches to teaching at higher educational institutions in examples and tasks - Bukhkalo, Svіtlana Ivanovna; Ageicheva, Anna Oleksandrivna; Belyanskiy, Oleksandr Mykolaiyvych; Moskalenko, Maryna Volodymirivma; Derkunska, Zhanna Viktorivna; Iglin, Sergii Petrovuch (Національний технічний університет "Харківський політехнічний інститут", 2023)
The importance of teaching students at higher educational institutions by innovating study methods is investigated. Main innovative approaches were investigated. The usage of cases and projects in classes are studied. It is discussed that classic case promotes the development of independent decision-making skills, the second purpose of working with the case in the classroom is a communicative practice. It is described possible projects in the article. Innovative approaches for the formation of critical thinking skills is described in the article. It was determined that the systematic usage of the innovative approaches at higher educational institutions makes gave possibillity to effectively soft skills formation.

Досліджено важливість навчання студентів вищих навчальних закладів за інноваційними методами та основними інноваційні підходи. Вивчається використання кейсів і проектів на заняттях. Обговорюється, що класичний кейс сприяє розвитку навичок самостійного прийняття рішень, другою метою роботи з кейсом на уроці є комунікативна практика. У статті описані можливі проекти. У статті описано інноваційні підходи до формування навичок критичного мислення. Визначено, що систематичне використання інноваційних підходів у вищих навчальних закладах дає можливість ефективно формувати soft skills.
Інноваційні підходи викладання для закладів вищої освіти у прикладах і задачах
Keywords: case studies; project-oriented approach; innovative teaching approaches; pedagogy; foreign language; communication; innovative teaching technologies; кейс дослідження; проектно-орієнтований підхід; інноваційні підходи до навчання; педагогіка; іноземна мова; комунікація